2021
DOI: 10.21522/tijph.2013.09.01.art018
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Nature of Capacity Building Programs of HIV/AIDS Supply Chain Workforce in Nigeria

Abstract: This study on appraisal of nature of capacity building programs of HIV/AIDS supply chain workforce in Nigeria involved cross-sectional observational design. A pre-tested self-completion structured questionnaire was administered to 422 participants drawn from HIV/AIDS supply chain workforce. The survey had a response rate of 396(93.8%). The reliability statistics showed the questionnaire is reliable for nature of capacity building programs, Cronbach alpha (α = 0.886). On-the-job training was the most predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Most of the respondents were in the rank of manager, supervisor, specialist, advisor, and officer, with ages of many between 30 and 59 years and years of experience in the HIV/AIDS supply chain between 4 and 15 years. The respondents have significant experience with a good understanding of the supply chain management needs of the HIV/AIDS program [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the respondents were in the rank of manager, supervisor, specialist, advisor, and officer, with ages of many between 30 and 59 years and years of experience in the HIV/AIDS supply chain between 4 and 15 years. The respondents have significant experience with a good understanding of the supply chain management needs of the HIV/AIDS program [14].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that interventions that involved many stakeholders in the subject area have been effective in achieving sustainable practice change [18]. There has been an established relationship between training and employee performance, and effective capacitybuilding programs remain vital to improving supply chain systems [14,[20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation